Creatine Phosphokinase and Visual Analogue Scale as Indicators for Muscle Injury in Untrained Bodybuilders - Suresh Shanmugam; Reni Farenia; Nina Tristina (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Skeletal muscle is a vital tissue in the human body to enable breathing, walking and performing several sports activities. However, this muscle is persistently injured throughout every sports session. Some exercises demand a muscle injury occurrence in order to build a stronger muscle through an adaptation process namely bodybuilding exercise. Importantly, every muscle injury should occur within a physiological range which can be identified by several biomarkers as well as pain scale. The aim of this study was toidentify changes on the level of Creatine phosphokinase (CPK) and Visual analogue scale (VAS) between pre and post training sessions and the correlation between these two indicators.Methods: This was an observational analytical cross sectional comparison study which was conducted in October 2012 and the subjects were adult untrained bodybuilders at the Jatinangor fitness center. The data was obtained by measuring serum CPK and marked VAS. The data were analyzed by t-test, Wilcoxon’s test and Spearman’s correlation.Results: Both CPK and VAS increased significantly by 296 U/L and 19.9 mm respectively. There was a strong positive significant correlation between VAS and CPK (p=0.01, r = 0.711).Conclusion: The healthy untrained bodybuilders chosen in this study experienced a mild (<2000 U/L) muscle injury throughout the training sessions with general increased CPK levels and VAS measurement. [AMJ.2015;2(1):147–52]